2000
DOI: 10.1002/1097-0339(200007)23:1<19::aid-dc4>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

ThinPrep� pap test promotes detection of glandular lesions of the endocervix

Abstract: The objectives of this study were to evaluate 1) the detection rate of atypical glandular cells of undetermined significance of endocervical cell type (AGUS‐EC) and 2) the correlation between AGUS‐EC on cytology and biopsy results using the conventional Papanicolaou (Pap) smear test vs. the ThinPrep® Pap test (TPPT). Cervical‐vaginal samples processed by the conventional Pap smear for 11 mo in 1996–1997 were identified, as were TPPTs collected for the same interval in 1997–1998. Biopsy results were compared af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 14 publications
3
31
0
2
Order By: Relevance
“…However, it is still hard to advocate that claim because of the conflicting results. 18,19 The fact that the incidence of AC has not changed much since the advent of Pap smear screening suggests that new and better ways of diagnosing AC have to be found. It includes the upgrade of applied cytological research to improve the sensitivity to detect the precursor lesions of AC.…”
Section: Discussionsupporting
confidence: 75%
“…However, it is still hard to advocate that claim because of the conflicting results. 18,19 The fact that the incidence of AC has not changed much since the advent of Pap smear screening suggests that new and better ways of diagnosing AC have to be found. It includes the upgrade of applied cytological research to improve the sensitivity to detect the precursor lesions of AC.…”
Section: Discussionsupporting
confidence: 75%
“…23 However, seven of the false-negative TP results in that study were diagnosed as "endocervical atypia,"indicating, as the authors themselves stated, that the diagnostic criteria for AIS in TPs need refinement and that enhanced performance may be expected once they are learned. The results of the current study are similar to those of the two prior comparison studies using historic controls, 21,22 although our PPVs for AGUS were lower than those reported in either study for both TPs and CPs and were not significantly different. The lower PPVs that we observed may be due to our having included patients with only cytologic follow-up as well as those patients with biopsy follow-up, because lesions that are biopsied after a cytologic interpretation may be more likely to be neoplastic.…”
Section: Discussionsupporting
confidence: 88%
“…That report also assessed available prior cytologic results in patients with biopsy-confirmed adenocarcinoma or AIS and concluded that TP increased the sensitivity as well as the specificity for these lesions. Bai et al, 22 also using biopsy follow-up and historic CP controls, noted a 50% reduction in AGUS interpretations with TPs and a PPV of 40% for 35 TPs versus 26% for 72 CPs. A third study, using split-sample comparisons in 30 cases of cervical AIS, reported a lower sensitivity for TPs.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Other studies focus on the detection of atypical glandular cells of undetermined significance, [20][21][22][23][24] an imprecise term, which is recognized to yield more high-grade squamous lesions than high-grade endocervical glandular lesions. 22,[25][26][27] The concurrent presence of cells from an HSIL did not increase the sensitivity of cervical cytology; in fact, cytologists were less likely specifically to recognize a high-grade glandular lesion.…”
Section: Discussionmentioning
confidence: 50%